Full-length cDNA cloning and SNP discovery of xyloglucan endotransglycosylase/hydrolase (xth) and cellulose synthase (cesa) genes in a tropical timber tree (neolamarckia cadamba) - Tiong, Shing Yiing (Universiti Malaysia Sarawak (UNIMAS), 2014)
Neolamarckia cadamba or commonly known as Kelampayan is one of the fast growing forest tree species in Sarawak with high commercial value. The wood is used for producing different products such as plywood, pulp, paper, and furniture. This study was carried out as a part of a tree breeding and improvement programme for forest plantation. Since wood is composed of cell walls, studies on cell wall formation and regulation are important. Single nucleotide polymorphisms (SNPs) were chosen to determine the genetic variations of the xyloglucan endotransglycosylase/hydrolase (XTH) and the cellulose synthase (CesA) genes in N. cadamba. XTH and CesA are proteins that play an important role in regulating wood formation. XTH enzymes regulate cell wall expansion while CesA acts as a central catalyst in the generation of plant cell wall biomass (cellulose). Two full-length XTH cDNAs, namely NcXTH1 (JX134619) and NcXTH2 (JX134620) were discovered. The nucleotide sequences were 893 bp and 1,024 bp in length, respectively. The open reading frames for NcXTH1 and NcXTH2 were 858 bp and 915 bp, respectively. Results predicted that NcXTH1 and NcXTH2 proteins carry out XET activity but they were from different XTH family members. The hypothetical full-length CesA cDNA (NcCesA1; JX134621) was assembled by in silico analysis using the selected CesA cDNA sequences from NcdbEST and the amplified 5’- and 3’-RACE sequences. The NcCesA1 cDNA has a length of 3,472 bp with 3,126 bp open reading frame encoding 1,042 amino acids. Sequence analyses showed that NcCesA1 protein is involved in glycosyltransferation of the secondary cell wall cellulose biosynthesis. Wood properties (basic density) associated single nucleotide polymorphisms (SNPs) were discovered in the NcXTH1 and NcCesA1 genes. A total of 34 SNPs with 2.65% occurrence was found in 15 partial genomic DNA sequences of NcXTH1 with two SNPs significantly associated with wood basic density (p<0.05). For the NcCesA1 gene, only three SNPs were iv found in 15 partial targeted regions of the NcCesA1 DNA sequences (~779 bp). The low occurrence of SNPs (0.39%) in NcCesA1 showed no quantitatively significant association with wood basic density. In the linkage disequilibrium (LD) study, a total of 496 pairwise comparisons were estimated from the polymorphic sites (SNPs) detected in the NcXTH1 and NcCesA1 genes of N. cadamba with a mean R 2 value of 0.000687. The LD graph plotted decayed very slowly with distance of polymorphic sites in a consistent and linear pattern. In conclusion, this study showed an association between NcXTH1 genes with wood basic density.